Comparative study on analysis of the volleyball team service - Szabo-Alexi, M.; Mihaescu, C.; Stirbu, I. C.; Stirbu, C. M.; Szabo-Alexi, P. C. (Analele Universitatii din Oradea: Fascicula Educatie Fizica si Sport, 2022)
Currently, the game of volleyball is one of the most popular sports on the planet. With a number of practitioners exceeding 800 million people who play volleyball at least once a week, 900 million fans and more than 220 affiliated federations, volleyball ranks 5th in the world in a list of all sports. Unfortunately, at the beginning of 2020, the outbreak of the coronavirus affected different parts of the world. Without a doubt, the coronavirus has had and is having an impact on various aspects of our lives. Many industries have been affected by the coronavirus, and sports is one of them. It is worth noting that Covid 19 has had a profound negative impact on all sports. All the gyms were closed for a long time, and the athletes could no longer train. The most affected were athletes practicing team sports, therefore also volleyball players, both professionals and amateurs, who were not allowed to come together to practice and develop their skills. When the rapid spread of the coronavirus began, the leagues reacted very quickly. As a result, all local, national and international volleyball competitions were canceled within a short period of time. Also, the ongoing competitions were interrupted, without being resumed. The most affected by the pandemic were even the children's and junior clubs, many of them giving up playing volleyball. Athletes had to overcome a lot of challenges during the coronavirus outbreak as they had to continue training and developing their skills. Setting goals for the future, analyzing mistakes and correcting them, creating a schedule by setting tasks and prioritizing them, communicating online with coaches and teammates, or watching and analyzing interesting volleyball matches can be activities during such a period. After a period of over a year, in many countries gyms have started to reopen and things are returning to normal, with competitions resuming under certain conditions.